THE POEM’S USE OF IMAGERY AND SYMBOLISM*: DISCUSS THE WAYS IN WHICH YEATS EMPLOYS IMAGERY AND SYMBOLISM TO CONVEY THE POEM’S THEMES AND IDEAS. CHOOSE SPECIFIC EXAMPLES FROM THE POEM TO SUPPORT YOUR ANALYSIS. - Dr Sadhan Das; Animesh Nath (International Journal For Research In Educational Studies, 2025)
This study examines the use of imagery and symbolism in William Butler Yeats' poem "Sailing to Byzantium". Through a qualitative content analysis approach, the researcher analyzes the poem's language, imagery, and symbolism to identify themes and motifs related to aging, mortality, and the transcendent power of art. The study demonstrates how Yeats employs sensory imagery, symbolic landscapes, and mythological allusions to convey the speaker's quest for transcendence and eternal life. The findings of this study contribute to a deeper understanding of Yeats' poetry and the modernist movement, and highlight the importance of literary analysis in uncovering the complex meanings and themes that underlie great works of literature.